ISG15/USP18/STAT2 is a molecular hub regulating IFN I-mediated control of Dengue and Zika virus replication - Espada, Constanza Eleonora; da Rocha, Edroaldo Lummertz; Ricciardi-Jorge, Taissa; dos Santos, Adara Aurea; Soares, Zamira Guerra; Malaquias, Greicy; Patrício, Daniel Oliveira; Gonzalez Kozlova, Edgar; dos Santos, Paula Fernandes; Bordignon, Juliano; Sanford, Thomas J.; Fajardo, Teodoro; et al. (Frontiers in Immunology, 2024)
The establishment of a virus infection is the result of the pathogen's ability to replicate in a hostile environment generated by the host's immune system. Here, we found that ISG15 restricts Dengue and Zika viruses' replication through the stabilization of its binding partner USP18. ISG15 expression was necessary to control DV replication driven by both autocrine and paracrine type one interferon (IFN-I) signaling. Moreover, USP18 competes with NS5mediated STAT2 degradation, a major mechanism for establishment of flavivirus infection.Strikingly, reconstitution of USP18 in ISG15-deficient cells was sufficient to restore the STAT2's stability and restrict virus growth, suggesting that the IFNAR-mediated ISG15 activity is also antiviral. Our results add a novel layer of complexity in the virus/host interaction interface and suggest that NS5 has a narrow window of opportunity to degrade STAT2, therefore suppressing host's IFN-I mediated response and promoting virus replication.Disease is an emergent property that results from a microorganism's ability to replicate in a given host and the latter's immune response. Here we describe how the immunoregulatory function of ISG15 (an interferon stimulated gene) affects Dengue and Zika virus replication by occupying a niche used by the virus non-structural protein 5 (NS5) to evade host's immunity.In the absence of ISG15, NS5 efficiently degrades a main signaling hub of innate immunity (STAT2), leading to cell immune suppression and consequently virus growth. This sheds light into how flaviviruses intimately interact with the host immune system and could lead to a hostbased therapy target.